2001
DOI: 10.1522/12774896
|View full text |Cite
|
Sign up to set email alerts
|

Environmental impact of thallium related to the mercury-thallium-gold mineralization in southwest Guizhou Province China

Abstract: Toxic metals associated with metal mineralization and mining are critical targets for environmental studies. Thallium, as a typical toxic metal, has received less attention from a geo-environmental perspective since thallium deposits are relatively rare.This study focuses on natural accumulation of thallium associated with Hg-Tl-(Au) mineralization in the Lanmuchang area in southwest Guizhou Province, China, as a case study for thallium hazard in a geo-environmental perspective. It aims at understanding of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 88 publications
(167 reference statements)
0
3
0
Order By: Relevance
“…Higher community diversity index and richness index indicate that there is a longer food chain and more complex food web in the ecosystem, thus enhancing the stability of the community [ 54 , 55 ]. The diversity index of mites in different moss habitats in the study area is generally higher than that of mites in rose mixed agricultural forest, burning agricultural land and rosa roxburghii land in karst area [ 56 – 58 ], indicating that the ecological environment of mites in cave moss habitats is more stable than that of human disturbance. A lot of research shows that the diversity of mite community is related to the composition of vegetation components and the diversity of covering plants, and the quantity and nature of its litter may have a decisive impact on mite community [ 24 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Higher community diversity index and richness index indicate that there is a longer food chain and more complex food web in the ecosystem, thus enhancing the stability of the community [ 54 , 55 ]. The diversity index of mites in different moss habitats in the study area is generally higher than that of mites in rose mixed agricultural forest, burning agricultural land and rosa roxburghii land in karst area [ 56 – 58 ], indicating that the ecological environment of mites in cave moss habitats is more stable than that of human disturbance. A lot of research shows that the diversity of mite community is related to the composition of vegetation components and the diversity of covering plants, and the quantity and nature of its litter may have a decisive impact on mite community [ 24 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tl adsorption to Fe-Mn adsorbents is fast, efficient, and selective. Equilibrium adsorption can be achieved by over 95% at a wide range of the operating pH values (3)(4)(5)(6)(7)(8)(9)(10)(11)(12) and high ionic strengths (0.1-0.5 mol•L −1 ). This study demonstrates that the mechanism of Tl adsorption is mainly in the complexation of hydroxyl groups and Tl(I) on the Fe-Mn surface, as well as the oxidation of Tl(I) to Tl(III) and the generation of Tl 2 O 3 precipitates on the surface of the material to be adsorbed by the material [60].…”
Section: Thallium Removal By Iron Oxidesmentioning
confidence: 99%
“…Studies have shown that thallium contamination has posed a serious threat to drinking water safety, and the scope of contamination has spread to countries around the world [7][8][9]. In Canada, New Brunswick, the United Kingdom, Cornwall, Idaho, China, Qianxinan, Guangdong, and Xiangnan, as well as other waters near the mine and downstream water bodies, the monitoring value of drinking water thallium exceeded 10.2-10.4 times.…”
Section: Introductionmentioning
confidence: 99%